Brain disease and the study of learning disabilities in the Netherlands (c. 1950–85). - Bakker, Nelleke (Paedagogica Historica, 2015)
This paper discusses the role brain disease has played in the discourse and practices of child scientists involved in the study of learning disabilities and behavioural disorders from the 1950s up to the mid-1980s, particularly in the Netherlands as part of a developing international scientific community. In the pre-ADHD era, when child sciences established themselves as academic fields of study and special education expanded quickly, brain-related psychiatric labels like “minimal brain damage” (MBD, later “dysfunction”) were often used for inattentive or hyperactive children. These diagnoses seem to have contributed to the academic status of the developing field of study by connecting neurological research into brain dysfunction with the study of learning problems and their treatment. The increasing differentiation between medical and educational research provided opportunities for those who focused on the development of American-style treatment such as behaviouristic conditioning. By 1980, more than a decade after their Anglo-American colleagues had done so, Dutch child scientists had finally lost confidence in the unspecific and overinclusive MBD label. Its popularity among the larger public, as well as concern about the rapidly growing number of diagnoses, continued to stimulate demand for more research into the nature of learning disabilities and methods of remedial teaching.